The Relationship between I Love You Massage and Decreased Frequency of Colic in Bloated Infants - Debora Paninsari; Riris Talenta Situmorang; Roma Ria Br. Sitohang; Novi Adies Adelia; Nur Indah Giawa; Okta Elvina Marpaung (Indonesian Journal of Global Health Research, 2025)
Infantile colic or also known as colic in infants is when a healthy baby experiences bloating and crying loudly for no apparent reason. One way to get rid of the disorder in the form of flatulence and colic pain in infants is to provide massage techniques which are gentle stroking movements on the abdomen that resemble the letters “I” “L” and “U”, helping digestive health and improving the digestive system. Objective: This study aims to see the relationship of I Love You massage with a decrease in the frequency of colic in bloated babies at the Siti Hajar midwife clinic in Medan Marelan. Methods: This type of research is Quantitative research with Correlation design research design. The population is all babies who experience bloating as many as 40 babies. The sampling method used Non Probability Sampling with Accidental Sampling type as many as 36 bloated babies, carried out using observation sheets and interviews. With data analysis using the Chi Square test. Results: The results of this study indicate that the p value = 0.000 <0.005 so that the null hypothesis (H0) is rejected. Conclusion: there is a relationship between I Love You massage with a decrease in frequency in baby bloating.